Aortic Balloon Valvuloplasty Prior to Orthotopic Liver Transplantation: A Novel Approach to Aortic Stenosis and End-Stage Liver Disease - Edward Coverstone; Kevin Korenblat; Jeffrey S. Crippin; William C. Chapman; Andrew M. Kates; Alan Zajarias (Case Reports in Cardiology)
The combination of severe aortic stenosis and end-stage liver disease increases the morbidity and mortality of surgical aortic valve replacement or orthotopic liver transplantation resulting in a prohibitive operative risk. We propose a staged approach of balloon aortic valvuloplasty prior to orthotopic liver transplantation as a bridge to definitive aortic valve replacement. Between 2010 and 2012, four patients with severe aortic stenosis and end-stage liver disease underwent staged balloon aortic valvuloplasty followed by orthotopic liver transplantation. All patients had been deemed to be inappropriate candidates for liver transplantation or aortic valve surgery due to their comorbidity. One patient died of complications from a perivalvular abscess. Three patients went on to successful graft implantation and function and surgical recovery. Two of the three patients proceeded to definitive surgical aortic valve replacement with the remainder currently undergoing evaluation. In this case series, we present a novel approach of balloon aortic valvuloplasty prior to liver transplantation as a potential bridge to definitive treatment of severe aortic stenosis in the end-stage liver patient.